1972
DOI: 10.1111/j.1365-2362.1972.tb00650.x
|View full text |Cite
|
Sign up to set email alerts
|

Serum Vitamin B12 Binding Proteins in Viral Hepatitis

Abstract: Abstract. Sera from patients with viral hepatitis were examined for serum vitamin B12 concentration, unsaturated B12 binding capacity, total B12 binding capacity of whole serum and of separate transcobalamin‐I and transcobalamin‐II fractions. It was found that the high serum B12 concentrations observed were associated with an increase in the B12 binding of the transcobalamins. The B12 bound to transcobalamin‐I was found to be two to three times higher than that in normal subjects. The most striking difference… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
6
0

Year Published

1974
1974
2004
2004

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(6 citation statements)
references
References 13 publications
0
6
0
Order By: Relevance
“…The most important change was the decrease in the TC I and increase in the TC II associated with re duction in the bound serum B12. The latter findings were observed in hepatocellu lar damage [ 16].…”
Section: Case Reportmentioning
confidence: 52%
“…The most important change was the decrease in the TC I and increase in the TC II associated with re duction in the bound serum B12. The latter findings were observed in hepatocellu lar damage [ 16].…”
Section: Case Reportmentioning
confidence: 52%
“…An in crease in plasma vitamin B12 levels has also been reported in other liver disorders, e.g. viral hepatitis [12,24] and alcoholic hepati tis where hepatic cytolysis is a common fea ture [5], In the same way, Baker et al [5] observed recently that high plasma vitamin B12 levels correlated significantly with the standard liver function tests, including bili rubin, cholylglycin, alkaline phosphatase, al anine serum transferase and prothrombin time, in case of alcoholic hepatitis. They concluded that the increased plasma vitamin B12 levels were correlated to the severity and the mortality of alcoholic hepatitis.…”
Section: Discussionmentioning
confidence: 97%
“…Rachmilewitz et al [12] have shown that induced liver injury in dogs and rats results in a release of Cbl from damaged hepatocytes. This may account for elevated serum Cbl [6,7], Moreover, the ability of the alco holic liver to store vitamin may be impaired in alcoholic cirrhosis [23], In our study, the levels of total corrinoids and of true Cbl in IVC, SHV and SVC from 27 cirrhotic pa tients were significantly higher than in con trols and they increased with the degree of severity of the disease, estimated by the Child-Pugh classification ( fig.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations